1946
DOI: 10.1021/i560149a010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Estimation of Free Fatty Acids in Dried Egg Powders

Abstract: At the normal pH of dried whole egg, fatty acids liberated during storage are incompletely estimated by the A.O.A.C. procedure for determination of acidity of the ether extract. In addition, the contribution of the extracted cephalin to the acidity of the ether extract may obscure significant percentage increases in the free fatty acidity of the egg powder. The necessity for drying the egg powder as required in the A.O.A.C. procedure is re-emphasized. the liberated fatty acid, whether present as the free acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1946
1946
1963
1963

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The remainder of the lipid nitrogen is usually reported as 'kephalin', but direct determination of the amino nitrogen has indicated considerably higher values, e.g. 42 % (Chargaff, Ziff& Rittenberg, 1942), 38 % (Kline & Johnson, 1946), 35 % (Kline, Gegg & Sonoda, 1951) and 9 4, 20 and 32 % (Sulser, 1954). Chargaff et al (1942) used a direct van Slyke determination on the intact phospholipid, a procedure known to be subject to interference by the unsaturated acids present (Lea & Rhodes, 1954).…”
mentioning
confidence: 99%
“…The remainder of the lipid nitrogen is usually reported as 'kephalin', but direct determination of the amino nitrogen has indicated considerably higher values, e.g. 42 % (Chargaff, Ziff& Rittenberg, 1942), 38 % (Kline & Johnson, 1946), 35 % (Kline, Gegg & Sonoda, 1951) and 9 4, 20 and 32 % (Sulser, 1954). Chargaff et al (1942) used a direct van Slyke determination on the intact phospholipid, a procedure known to be subject to interference by the unsaturated acids present (Lea & Rhodes, 1954).…”
mentioning
confidence: 99%
“…fEuorescens in egg liquid a t a minimum before lyophilization, so that the effects of growth products would not be confused with those formed subsequent to drying and during storage. No measurable growth (repEoduction of bacteria) took place in the powders during storage-in fact, the viable counts 'It seems desirable to point out that the Kline and Johnson (1946) method for estimating free fatty acid content excludes lactic acid as a factor in acidity.…”
Section: Bacteria On Quality Of Stored Lyophilized Eoq Powders 389mentioning
confidence: 99%
“…Hydrogen-ion concentrations were determined on 1 : 10 dilutions of the powder in distilled water. Free fatty acid content was determined by the procedure recommended by Kline and Johnson (1946). For palatability values the reconstituted powder was mixed with equal parts of fresh shell egg and cooked over water at 87.8"C.(19OoF.…”
mentioning
confidence: 99%
“…It was subsequently observed that such loss estimates were likeiy to be in error on account of the demonstrated tendency for phosphatides to absorb alkali during the free fatty acid titration (4). Further study revealed the fact that the free fatty acid had a slight depressing effect upon the phosphatide estimates arrived at by the acetone-insoluble method.…”
mentioning
confidence: 99%
“…The free fatty acid and acetone-insoluble errors would normally tend to compensate for one another to some extent but not completely in all eases. The data shown in Table I were compiled to check the reported effect of phosphatides upon the free fatty acid results (4). In this case a 2% solution of acetic acid in acetone was used to precipitate the phosphatides from cottonseed oil because, as will be demonstrated later, pure acetone will usually retain most of these compounds in solution or suspension.…”
mentioning
confidence: 99%